NWRA AVOSS Wake Vortex Prediction Algorithm Version 3.1.1 (Tech Briefs, 2018)
The Northwest Research Associates Aircraft Vortex Spacing System Prediction Algorithm computes trailing vortex trajectories and circulation decay in a plane perpendicular to the path of the aircraft that has generated the vortices. Underlying the algorithm are the following assumptions: initial vortex conditions assume that all trailing vorticity due to lift is rolled up into a vortex pair; away from the ground, the vortices are transported laterally at the speed of the local crosswind, and transport due to large-scale turbulence is not included; crosswind shear effects are not included, except as might arise from the previous assumption; and the circulation decay rate for each member of the vortex pair is the same. For the purpose of the algorithm, the vortices are considered to evolve through four distinct phases.